BL‐8040 CXCR4 antagonist is safe and demonstrates antileukemic activity in combination with cytarabine for the treatment of relapsed/refractory acute myelogenous leukemia: An open‐label safety and efficacy phase 2a study. Issue 8 (3rd December 2020) - Borthakur, Gautam; Ofran, Yishai; Tallman, Martin S.; Foran, James; Uy, Geoffrey L.; DiPersio, John F.; Showel, Margaret M.; Shimoni, Avichai; Nagler, Arnon; Rowe, Jacob M.; Altman, Jessica K.; Abraham, Michal; et al.
Abstract : Background: CXCR4 mediates the retention and survival of acute myelogenous leukemia blasts in bone marrow and contributes to their resistance to chemotherapy. The authors evaluated a combination of the high‐affinity CXCR4 antagonist BL‐8040 with high‐dose cytarabine (HiDAC) chemotherapy in a phase 2a study of patients with relapsed and refractory AML. Methods: Forty‐two patients received treatment with BL‐8040 monotherapy for 2 days followed by a combination of BL‐8040 with HiDAC for 5 days. Six escalating BL‐8040 dose levels were investigated (0.5, 0.75, 1.0, 1.25, 1.5, and 2.0 mg/kg), and 1.5 mg/kg was selected as the dose for the expansion phase (n = 23). Results: BL‐8040 in combination with HiDAC was safe and well tolerated at all dose levels. Clinical response was observed with BL‐8040 doses ≥1.0 mg/kg. The composite response rate (complete remissions plus complete remissions with incomplete hematologic recovery of platelets or neutrophils) was 29% (12 of 42) in all patients and 39% (9 of 23) in the 1.5‐mg/kg phase. The median overall survival was 8.4 months for all patients, 10.8 months in the 1.5‐mg/kg phase, and 21.8 months for responding patients in the 1.5‐mg/kg cohort. Two days of BL‐8040 monotherapy triggered the mobilization of blasts into peripheral blood, with significantly higher mean fold‐changes in responders versus nonresponders. This was accompanied by a decrease in bone marrow blasts. Conclusions: The current results demonstrate the efficacy of CXCR4 targeting with BL‐8040 and support continued clinical development in acute myelogenous leukemia. Abstract : BL‐8040 is a high‐affinity CXCR4 inhibitor. Combined with cytarabine, BL‐8040 treatment results in improved composite complete response rates and median overall survival in hard‐to‐treat patients with relapsed/refractory acute myelogenous leukemia.